Initial Laparotomy Versus Peritoneal Drainage in Extremely Low Birthweight Infants With Surgical Necrotizing Enterocolitis or Isolated Intestinal Perforation: A Multicenter Randomized Clinical Trial. Issue 4 (October 2021) - Blakely, Martin L.; Tyson, Jon E.; Lally, Kevin P.; Hintz, Susan R.; Eggleston, Barry; Stevenson, David K.; Besner, Gail E.; Das, Abhik; Ohls, Robin K.; Truog, William E.; Nelin, Leif D.; Poindexter, Brenda B.; et al.
Abstract : Objective: The aim of this study was to determine which initial surgical treatment results in the lowest rate of death or neurodevelopmental impairment (NDI) in premature infants with necrotizing enterocolitis (NEC) or isolated intestinal perforation (IP). Summary Background Data: The impact of initial laparotomy versus peritoneal drainage for NEC or IP on the rate of death or NDI in extremely low birth weight infants is unknown. Methods: We conducted the largest feasible randomized trial in 20 US centers, comparing initial laparotomy versus peritoneal drainage. The primary outcome was a composite of death or NDI at 18 to 22 months corrected age, analyzed using prespecified frequentist and Bayesian approaches. Results: Of 992 eligible infants, 310 were randomized and 96% had primary outcome assessed. Death or NDI occurred in 69% of infants in the laparotomy group versus 70% with drainage [adjusted relative risk (aRR) 1.0; 95% confidence interval (CI): 0.87–1.14]. A preplanned analysis identified an interaction between preoperative diagnosis and treatment group ( P = 0.03). With a preoperative diagnosis of NEC, death or NDI occurred in 69% after laparotomy versus 85% with drainage (aRR 0.81; 95% CI: 0.64–1.04). The Bayesian posterior probability that laparotomy was beneficial (risk difference <0) for a preoperative diagnosis of NEC was 97%. For preoperative diagnosis of IP, death or NDI occurred in 69% after laparotomy versus 63% with drainage (aRR, 1.11; 95% CI: 0.95–1.31); Bayesian probability of benefit with laparotomy = 18%. Conclusions: There was no overall difference in death or NDI rates at 18 to 22 months corrected age between initial laparotomy versus drainage. However, the preoperative diagnosis of NEC or IP modified the impact of initial treatment. Abstract : Supplemental Digital Content is available in the text